2003
DOI: 10.1046/j.1600-0420.2003.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular blood flow of the optic nerve head and peripapillary retina in unilateral exfoliation syndrome

Abstract: ABSTRACT.Purpose: To measure microvascular blood flow in patients with unilateral exfoliation syndrome (XFS) without glaucoma or ocular hypertension and to compare the values in the eyes with clinically detected exfoliation, their nonexfoliative fellow eyes of the same patients and control eyes. Methods: Twenty-two patients with clinically detected unilateral XFS and 30 age-matched healthy subjects were included in this study. Group 1 consisted of 22 eyes with clinical XFS, and the nonexfoliative fellow eyes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 25 publications
2
35
1
6
Order By: Relevance
“…It may be argued that the differences between the results of the Yü ksel study and our results may be due to the use of topical therapy in the Yü ksel study. Although several papers have reported systemic and ocular vascular alterations in patients with pseudoexfoliation syndrome, [20][21][22][23] our results suggested that the OBF alterations were stronger in the POAG patients group.…”
Section: Discussioncontrasting
confidence: 77%
“…It may be argued that the differences between the results of the Yü ksel study and our results may be due to the use of topical therapy in the Yü ksel study. Although several papers have reported systemic and ocular vascular alterations in patients with pseudoexfoliation syndrome, [20][21][22][23] our results suggested that the OBF alterations were stronger in the POAG patients group.…”
Section: Discussioncontrasting
confidence: 77%
“…6 The cellular stress conditions such as oxidative stress, inflammation, ischemia and hypoxia play a role in the pathophysiology of PEXS and PEXG. 7,8 A clear role for inflammatory mediators and cells has been established in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The inflammation is an important component of various age-related diseases such as: Alzheimer's disease and atherosclerosis. 6 The role of neutrophil/lymphocyte ratio (NLR) in cardiovascular and cancer diseases has been reported 4,5 but the relation with the ocular diseases is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Ayrıca, oküler kan akımını azalttığına dair çalış-malar mevcuttur. 5,6,[13][14][15] Yüksel ve ark., PEX sendromlu ve PEX glokomlu hastalarda retrobulber kan akımında deği-şiklikler saptamış, kan akım velositesinde azalma ve vasküler rezistansta artış olduğunu göstermiş, bu bulguların PEX materyalinin damar duvarlarında birikmesi sonucu olduğunu ileri sürmüşlerdir. 5 Ocakoğlu ve ark.…”
Section: Gereç Ve Yöntemlerunclassified
“…[10][11][12] Literatürde çalışmalar olmakla birlikte, psödoeksfo-liatif materyalin koroid kan akımı ve koroid kalınlığına etkisi tartışmalıdır. 5,6,[13][14][15][16][17][18][19][20][21][22] Bu çalışmada, PEX sendromlu hastalarda ve sağlıklı bireylerde makuler koroid kalınlığının değerlendirilip sağlıklı gözlerle karşılaştırılması amaçlanmıştır.…”
unclassified